Edukasi Seks Sejak Dini: Kematangan Identitas Gender Di Fase Phallic - Iftitahun Nabilah; Shibi Zuhroul Mardliyah; Jami’atul Hasanah (EQUALITY: Journal of Gender, Child, and Humanity Studies, 2025)
Toddlers, as the nation’s future generation, are in a crucial developmental stage between the ages of 0–6 years. However, the increasing incidence of sexual abuse among toddlers indicates a critical lack of understanding and implementation of developmentally appropriate early childhood sex education. This condition calls for a critical examination of the appropriate timing and approach to strengthening children’s gender identity. This study aims to analyze the importance of reinforcing gender identity in toddlers during the phallic stage based on psychosexual development theory. The research method employed is a qualitative literature review, examining relevant books and scholarly articles. The findings indicate that the phallic stage plays a significant role in the formation of healthy gender identity through children’s processes of identification and understanding of gender roles. Appropriate sex education during this stage can serve as a preventive measure against sexual violence and sexual deviation. This study contributes a conceptual foundation for educators and parents in designing early childhood sex education aligned with children’s psychological development.